The Galesia trilogy and selected manuscript poems of Jane Barker - Barker, Jane (Women writers in English 1350-1850., 1997)
Novelist, religious convert, political poet and sometime Jacobite spy, Barker wrote prolifically on a remarkable variety of subjects. "A Patch-Work Screen for the Ladies" (1723) and "The Lining of the Patch-Work Screen" (1726) achieved immense popularity upon first appearance